1979
DOI: 10.1093/oxfordjournals.aje.a112684
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Brain Tumors in Children

Abstract: An exploratory case-control study was conducted in 15 hospitals in the Baltimore, MD, SMSA of possible etiologic factors associated with brain tumors in children. Eighty-four children with brain tumors were compared to normal children and to children with other malignancies. Parents of these children were interviewed about a variety of possible etiologic factors. The findings included: 1) children with brain tumors as well as children with other cancers had a greater tendency than normal children to have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
3
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(104 citation statements)
references
References 0 publications
4
94
3
3
Order By: Relevance
“…Schwartzbaum et al, (1991) reported no association between parental use of pesticides in the garden between birth and diagnosis of Wilms' tumour (OR = 0.7, P = 0.30), whereas Olshan et al (1993) found a significant association between this tumour and household extermination of insects or pests in the 3 years before diagnosis (OR = 2.2, 95% CI = 1.2-3.8). Other studies have suggested that living on a farm during childhood or exposure to pesticides within the home environment may be associated with childhood bone cancer, brain cancer and leukaemia (Gold et al, 1979;Lowengart et al, 1987;Schwartzbaum et al, 1991;Buckley et al, 1994;Cordier et al, 1994;Leiss and Savitz, 1995;Meinert et al, 1996) and environmental pollution with pesticides has been suggested as a possible cause of childhood leukaemia in The Netherlands (Mulder et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Schwartzbaum et al, (1991) reported no association between parental use of pesticides in the garden between birth and diagnosis of Wilms' tumour (OR = 0.7, P = 0.30), whereas Olshan et al (1993) found a significant association between this tumour and household extermination of insects or pests in the 3 years before diagnosis (OR = 2.2, 95% CI = 1.2-3.8). Other studies have suggested that living on a farm during childhood or exposure to pesticides within the home environment may be associated with childhood bone cancer, brain cancer and leukaemia (Gold et al, 1979;Lowengart et al, 1987;Schwartzbaum et al, 1991;Buckley et al, 1994;Cordier et al, 1994;Leiss and Savitz, 1995;Meinert et al, 1996) and environmental pollution with pesticides has been suggested as a possible cause of childhood leukaemia in The Netherlands (Mulder et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Specific exposures suggested for specific sites or types of cancer other than ALL had, by 1990, included: chloramphenicol (Shu et al, 1987) and maternal drug use prior to or during pregnancy in relation to acute non-lymphoblastic leukaemia (Robison et al, 1989) barbiturates, and parental exposure to substances such as solvents (Gold and Gordis, 1978;Gold et al, 1979) and N-nitroso compounds (Preston-Martin et al, 1982) for central nervous system (CNS) tumours; and maternal exposures during or just prior to pregnancy to drugs (including recreational drugs and anti-convulsants), alcohol and hair colourants for neuroblastoma (Lipson and Bale, 1985;Kramer et al, 1987) and for Wilms' tumour (Bunin et al, 1987). It had also been suggested that Hodgkin's disease in children might arise as a rare sequel to infection with a common virus (Gutensohn and Cole, 1981;Gutensohn and Shapiro, 1982) and that children with rhabdomyosarcoma were less likely to be immunized than controls (Grufferman et al, 1982;Hartley et al, 1988).…”
Section: Originmentioning
confidence: 99%
“…As well antinausea medication, kerosene, pesticides (including the use of pest strips), herbicides and fertilizers have been associated with increased risk (Shu et al 1996, Robison et al 1995, Leiss and Savitz, 1995, Infante-Rivard 1997, Steinbuch 1994, Sarasua and Savitz, 1994, Lowengart et al 1987, Buckley et al 1989, Pershagen et al 1992, Golding et al 1990, Kuijten et al 1990, Kuijten and Bunui 1993, Bunin et al 1994 Davis et al 1992), therapeutic doses of X-rays to the head, such as in the treatment for tinea capitis (Ron et ai. 1988), head and neck trauma to the child (Howe et al 1989), higher birth weight (Kuijten et al 1990, Gold et al 1979), consumption of Nnitroso compounds such as those allegedly found in hot dogs ( Sarasua and Savitz 1994), and being treated with cranial irradiation for leukemia (Chow et al 1996).…”
Section: Materna1 Exposures and Childhood Cancermentioning
confidence: 99%